Antiviral Activity of Feline BCA2 Is Mainly Dependent on Its Interference With Proviral Transcription Rather Than Degradation of FIV Gag - Qu, Meng; Wang, Weiran; Li, Weiting; Cao, Jiaming; Zhang, Xin; Wang, Chu; Wu, Jiaxin; Yu, Bin; Zhang, Haihong; Wu, Hui; Kong, Wei; Yu, Xianghui (Frontiers in Microbiology, 2020)
Human BCA2/RNF115/Rabring7 (hBCA2) is a RING type E3 ubiquitin ligase with the ability of autoubiquitination or promoting protein ubiquitination. It also acts as a host restriction factor has BST2-dependent and BST2-independent antiviral activity to inhibit the release of HIV-1. In a previous study, we demonstrated that feline BCA2 (fBCA2) also has E3 ubiquitin ligase activity, although its antiviral mechanism remained unclear. In this study, we showed that fBCA2 can interact with feline BST2 (fBST2) and exhibits an fBST2-independent antiviral function, and the RING domain is necessary for the antiviral activity of fBCA2. fBCA2 could degrade HIV-1 Gag and restrict HIV-1 transcription to counteract HIV-1 but not promote the degradation of HIV-1 through lysosomal. Furthermore, for both fBCA2 and hBCA2, restricting viral transcription is the main anti-FIV mechanism compared to degradation of FIV Gag or promoting viral degradation. Consequently, transcriptional regulation of HIV or FIV by BCA2 should be the primary restriction mechanism, even though the degradation mechanism is different when BCA2 counteracts HIV or FIV. This may be due to BCA2 has a special preference in antiviral mechanism in the transmission of primate or non-primate retroviruses.